2018
DOI: 10.1038/s41419-018-0990-2
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of stable iPS-derived human neural stem cell lines suitable for cell therapies

Abstract: Establishing specific cell lineages from human induced pluripotent stem cells (hiPSCs) is vital for cell therapy approaches in regenerative medicine, particularly for neurodegenerative disorders. While neural precursors have been induced from hiPSCs, the establishment of hiPSC-derived human neural stem cells (hiNSCs), with characteristics that match foetal hNSCs and abide by cGMP standards, thus allowing clinical applications, has not been described. We generated hiNSCs by a virus-free technique, whose propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 63 publications
2
35
0
Order By: Relevance
“…S1B). The quantitative RT-PCR assay further confirmed that the proportion of OTX2 expression was nearly ten-fold higher than that of NANOG and ESRRB in the piPSC-dox line that was generated in our lab and reported previously [29] (Fig. 1B).…”
Section: Conjoint Analysis Of Pipsc Rna and Mirna Transcriptomessupporting
confidence: 86%
See 1 more Smart Citation
“…S1B). The quantitative RT-PCR assay further confirmed that the proportion of OTX2 expression was nearly ten-fold higher than that of NANOG and ESRRB in the piPSC-dox line that was generated in our lab and reported previously [29] (Fig. 1B).…”
Section: Conjoint Analysis Of Pipsc Rna and Mirna Transcriptomessupporting
confidence: 86%
“…The piPSC-dox cells generated in this laboratory were cultured in LF2i medium [29], which included DMEM (Hyclone, USA) supplemented with 15% FBS (SeraPro, Germany), 0.1 mM nonessential amino acids (NEAA, Gibico, USA), 1 mM L-glutaMAX (Gibico, USA), 10 ng/mL LIF (Merck Millipore, USA), 10 ng/mL bFGF (PeproTech, USA), 0.1 mM β-mercaptoethanol (β-met, Sigma Aldrich, USA), 3 µM CHIR99021 (StemRD, USA), 2 µM SB431542 (StemRD. USA), 1 μg/mL doxycycline (Dox, Sigma Aldrich, USA).…”
Section: Cell Culturementioning
confidence: 99%
“…Further studies are needed to explore this possibility, as it could have implications for future applications. Indeed, we cannot rule out that this contributed to the low in vivo survival in nude mice in our experiment compared with published rates of 40% for iPS‐NSCs or 20% for fetal NSCs 38 …”
Section: Discussionmentioning
confidence: 65%
“…Three animals were sacrificed at 3 weeks to assess survival and proliferation and seven animals were sacrificed at 6 months. Transplantation experiments and analyses were performed as previously described for fetal NSCs 29,38 . For immunohistochemical analysis, brains were perfused‐fixed with ice‐cold 4% paraformaldehyde (Sigma #158127), postfixed overnight, cryoprotected and sectioned in a cryostat.…”
Section: Methodsmentioning
confidence: 99%
“…Due to their ability to self-renew and differentiate into the nervous tissue, they offer signi cant therapeutic potential in the treatment of neurological diseases such as spinal cord injury (SCI) [2], Alzheimer's disease (AD) [3], and Multiple sclerosis (MS) [4]. However, many currently available cell lines present us with severe obstacles relating to donor tissue acquisition, heterogeneity, availability, and related technical or ethical issues [5]. Besides,it is essential that cells must be transported from one place to another around the world for research and treatment.…”
Section: Introductionmentioning
confidence: 99%